L’outarde et le TGV : une controverse sur les compensations pour atteintes à la biodiversité - Jean-Christophe Vandevelde (VertigO)
Biodiversity offsets consist for developers in repaying a debt created by the impacts of their projects, after having avoided and reduced them as much as possible. Nevertheless, the actual implementation of these offsets is subject to uncertainty regarding their effectiveness and offsets have become an object of controversies. The study of the several stages constituting a controversy on offsets for a protected bird species shows that scientific and technical uncertainties around the ways to offset impacts are completed by another driving force for controversy, a strategic level where social actors defend their own interests. Taking into account these two drivers for controversy, it is possible to reconsider the role of expertise, called in to “objectify” that controversy. We showed that the expertise was not a contribution for building valid biodiversity offsets but had above all the role of helping the state to solve a dispute between the developer and the wildlife associations, a step necessary to allow the pursuit of the project.